Islam & housing - Omer, Spahic (A.S. Noordeen, 2010)
The house is a microcosm of culture and civilization because the primary elements of society, individuals organized along with the family lines, are born, raised and educated in them. The strength of the institutions of the family and house denotes the strength of a society and the verve of its cultural and civilizational agenda. Similarly, frailties in the institutions of the family and house denote frailties in a society and in its cultural and civilizational agenda. The house dominion is where people rise and fall, that is to say, where people either succeed or fail in managing and conducting the most crucial aspects of their lives. Housing is where the epicenter of the rise and fall of cultures and civilizations lies.